PETA BAHASA EXPOSE POSTER PUSAT PEMBINAAN KARIER DAN KEWIRAUSAHAAN SEBAGAI PENYEMPURNAAN KURIKULUM PERGURUAN TINGGI - NFN Tubiyono (﻿Kantor Bahasa Provinsi Bangka Belitung, 2013)
This study aims to reveal languages that are required by local, national, and multinational company. In addition,this study also explores the information that is needed for language skills which required in the company.Quantitative data were collected as a secondary source and will be combined with the primary data from HumanResource Department of the company that cooperate with PPKK-UA. The result of this study is expected to beuseful for college students in order to prepare early on to face an increasingly competitive workforce in thefuture. College students are expected to design their own language skills which are required by both national andmultinational companies. In fact, college students are not only required to mastering language skills, but they arealso expected to practice it in everyday life, so that it will become a habit that will shape their character. For theinstitution, the result of this study may become one of the considerations for college students’ redesigncurriculum, so that it can be adapted in the demands of the labor market (the industry). Industry is not only forgetting high academic achievement index, but also require language skills, so it can give positive effect andcontribution to the intitutions.